Impact of paternal age on IVF and pregnancy outcomes with only normal sperm parameters - Nobuyuki Kidera; Tomonori Ishikawa; Toshihiro Kawamura; Naoyuki Miyasaka (Elsevier, 2022)
Objective: Previous reports on advanced paternal age effects on assisted reproductive technology (ART) vary considerably and those on frozen-thawed embryo transfer (FET) are rare. We investigated whether paternal age affects in vitro fertilisation (IVF) and FET pregnancy outcomes. Materials and methods: 1657 IVF cycles performed from January 2014 to May 2018 were retrospectively investigated excluding cases of poor semen parameters. Paternal and maternal ages were categorised into groups, namely, <35, 35-39 and ≥ 40 years, to compare normal fertilisation (2 PN (pronuclei)) and high-quality blastocyst rates. Furthermore, 741 FET cycles were investigated and pregnancy, live birth and miscarriage rates were compared. Results: For the maternal age group (35-39), the 2 PN rate was significantly higher with paternal age group of <35 than groups of 35-39 and ≥ 40 (median%, <35 vs. 35-39 vs. ≥40 = 100.0 vs. 71.4 vs. 77.7; P = 0.005). The miscarriage rate was significantly higher with paternal age group of ≥40 than that of <35 and 35-39 when maternal age was <35 (median %, <35 vs. 35-39 vs. ≥40 = 13.1 vs. 7.8 vs. 33.3; P = 0.038). Conclusion: Our findings show that when maternal age was <35, advanced paternal age reduces the normal fertilisation rate and increases the FET miscarriage rate when maternal age was 35-39.